FTIR spectroscopy of methane adsorption on zeolites - Nor Kamarudin, Khairul Sozana (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
Adsorption of gases onto zeolites studied by various methods revealed the important of zeolite physical and structural properties such as pore network system, pore size, and surface area. The effect of zeolite properties on methane adsorption was investigated using ZSM-5, mordenite, ferrierite, zeolite beta, and faujasite-type zeolites (NaX, NaY, and NaYSI8) as adsorbents. The adsorbed methane was detected in the region between 3200 - 1200 em" using Fourier Transform Infrared (FTIR) spectrometer. The experimental results show that surface area is not the only factor that determines methane adsorption, in fact, the type of pore network system of the adsorbent also affects the adsorption of methane on zeolite. It also suggests that zeolites such as NaX and NaY are potential methane adsorbents.